In vivo Evaluation of Fibrous Collagen Dura Substitutes - Liu, Wenbo; Wang, Xin; Su, Jinlei; Jiang, Qingsong; Wang, Jing; Xu, Yang; Zheng, Yudong; Zhong, Zhihui; Lin, Hai (Frontiers in Bioengineering and Biotechnology, 2021)
Dura substitutes are applied in duraplasty to repair lost or damaged dura. Collagen-based dura substitutes are mainstream products in both the US and Chinese markets. In this study, dura substitute devices with potential dura regeneration ability are evaluated. The dura substitutes are composed of fibrous type I collagen that were purified from bovine tendon. Physical and chemical characterization demonstrated that the tested dura substitute has desirable porous scaffolding structures and is composed of highly purified type I collagen. The collagen dura substitutes were further investigated in vivo with a rabbit model for 6 months to evaluate their safety and performance to repair and regenerate dura. No inflammation or infection was observed during the course of in vivo study. The integration of the collagen dura substitutes with surrounding tissue was normal as compared to native tissue. The macroscopic and microscopic histological assessments of the sampled animal tissue showed that the damaged dura were regenerated. The collagen dura substitutes were resorbed between 3 and 6 months along with newly regenerated dura. Both tissue adhesion and dura repair was the worst in blank control group as compared to those in the collagen dura substitutes. Taken together, regenerative collagen dura substitutes demonstrated with suitable physicochemical properties. The in vivo evaluation in a rabbit model further demonstrated the safety and performance of such substitutes for dura repair and regeneration.